Influence of Thermal Oxidation on Processes of Charge Carrier Transfer in Porous Silicon - I.B. Olenych (Журнал нано- та електронної фізики)
The temperature dependences of the electrical conductivity of porous silicon and thermally oxidized porous silicon in the modes of direct and alternating currents in the temperature range of 80-370 K are investigated. The results are analyzed within the model of disordered semiconductors and the mechanisms of charge transfer are determined. Based on the spectra of thermally stimulated depolarization, the localized electron states which influence the electric transport properties of porous silicon are found. It is shown that thermal oxidation leads to the change in the occupation density of states in different energy ranges and expansion of the temperature range, in which hopping conductivity mechanism of porous silicon is realized.